2017
DOI: 10.1007/s12272-017-0894-1
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the reactions of 3,2′-polymethylene-2-phenylbenzo[b]-1,10-phenanthrolines with Ru(tpy)Cl3 and properties of the products

Abstract: A series of 3,2-polymethylene-2-phenylbenzo[b]-1,10-phenanthrolines was reacted with Ru(tpy)Cl to afford two ruthenium (Ru) complexes, a pentaaza-coordinated (N5Cl) complex [Ru(tpy)(L)Cl] and a hexa-coordinated (N5C) complex [Ru(tpy)(L)]. The ratio of these two complexes was found to be highly dependent on the length of the polymethylene bridge between terminal phenyl and central pyridine rings. The reaction between the dimethylene-bridged ligand and Ru(tpy)Cl afforded a hexa-coordinated (N5C) complex as an on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The PL spectrums were recorded by Hitachi fluorescence spectrophotometer F-7100. The synthetic procedure was according to the literature in previous work [39][40][41]. A mixture of R-phen (0.5 mmol), Ru(tpy)Cl 3 (220 mg, 0.5 mmol), and LiCl (105.4 mg 2.5 mmol) in EtOH: H 2 O (3:1, 50 mL) with Et 3 N (3 drops) was refluxed for 12 h. After that, the dark red reaction mixture was cooled to room temperature, then concentrated in vacuo.…”
Section: General Informationmentioning
confidence: 99%
“…The PL spectrums were recorded by Hitachi fluorescence spectrophotometer F-7100. The synthetic procedure was according to the literature in previous work [39][40][41]. A mixture of R-phen (0.5 mmol), Ru(tpy)Cl 3 (220 mg, 0.5 mmol), and LiCl (105.4 mg 2.5 mmol) in EtOH: H 2 O (3:1, 50 mL) with Et 3 N (3 drops) was refluxed for 12 h. After that, the dark red reaction mixture was cooled to room temperature, then concentrated in vacuo.…”
Section: General Informationmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13] Preclinical and clinical research showed that ruthenium (Ru) complexes could be alternatives to replace platinum drugs due to their advantages of low systemic toxicities and high efficacies in treating cancer patients. [14][15][16][17] In fact, promising Ru complexes, NKP-1019/IT-139 and NAMI-A, are in clinical trials as chemotherapeutic agents. Moreover, a polypyridyl complex, TLD-1433 as a photosensitizer is in phase II clinical trial for photodynamic therapy against bladder cancer.…”
Section: Introductionmentioning
confidence: 99%